An Efficient Criterion for Evaluating Fatigue Strength Improvement Through the Stop-Hole Technique - Bruno Atzori; Luca Vecchiato; Giovanni Meneghetti (Engineering Proceedings, 2025)
This study investigates the effect of a non-zero fillet radius, ρ, on the fatigue behaviour of notched components under uniaxial loading. A new diagram is introduced, which discusses the relationship between the notch tip radius and the fatigue limit. It also identifies a critical radius, ρ**, precisely marking the transition from sharp to blunt notch behaviour. Additionally, its application to the “stop-hole” technique is considered, where both material properties and geometric characteristics are analysed, demonstrating that introducing a fillet radius can improve fatigue resistance.